Psychometric Properties and Predictive Value of a Screening Questionnaire for Obstructive Sleep Apnea in Young Children With Down Syndrome - Grantham-Hill, Sarah; Evans, Hazel J.; Tuffrey, Catherine; Sanders, Emma; Elphick, Heather E.; Gringras, Paul; Kingshott, Ruth N.; Martin, Jane; Reynolds, Janine; Joyce, Anna; Hill, Catherine M.; Spruyt, Karen (Frontiers in Psychiatry, 2020)
Study objectives: Obstructive sleep apnoea (OSA) is common in children with Down syndrome and is associated with adverse health and cognitive outcomes. Daytime clinical assessment is poorly predictive of OSA, so regular screening with sleep studies is recommended. However, sleep studies are costly and not available to all children worldwide. We aimed to evaluate the psychometric properties and predictive value of a newly developed screening questionnaire for OSA in this population. Methods: 202 children aged 6 months to 6th birthday were recruited, of whomich 188 completed cardio-respiratory sleep studies to generate an obstructive apnoea hypopnoea index (OAHI). Parents completed the 14-item Down syndrome OSA screening questionnaire. Responses were screened, a factor analysis undertaken, internal consistency calculated and receiver operator characteristic (ROC) curves drawn to generate an area under the curve (AUC) to assess criterion related validity. Results: Of 188 children who completed cardiorespiratory sleep studies; parents completed the screening questionnaire for 186. Of this study population 15.4% had moderate to severe OSA defined by an OAHI of >5/hour. Sixty-three participants were excluded due to ‘unsure’ responses or where questions were not answered. Using the remaining 123 questionnaires a four-factor solution was found, with the 1st factor representing breathing related symptoms, explaining a high proportion of the variance. Internal consistency was acceptable with a Cronbach alpha of 0.87. ROC curves for the total score generated an AUC statistic of 0.497 and for the breathing subscale an AUC of 0.603 for moderate to severe OSA. Conclusion: A well designed questionnaire with good psychometric properties had limited predictive value to screen for moderate to severe OSA in young children with DS. The use of a screening questionnaire is not recommended. Screening for OSA in this population requires objective sleep study measures